Breaking the Chain of Figure Sacralization and Power Relations to Protect Students from Sexual Violence - Najmudin (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2026)
Sexual violence in religious educational institutions has reached an alarming level of emergency, threatening the safety of students and tarnishing the institution's integrity due to protection gaps within the social structures and organizational doctrines. The urgency of this issue lies in the